Long-Distance Access Network Design - Berger, Rosemary T.; Raghavan, S. (Management Science, 2004)
Long-distance telephone companies in the United States pay access fees to local telephone companies to transport calls that originate and terminate on their networks. These charges form the largest portion of the cost of providing long-distance service. Recent changes in the structure of access rates, which were mandated by the Federal Communications Commission (FCC), have created opportunities for long-distance companies to better manage access costs. In this paper, we develop an optimization-based approach to the economic design of access networks. Our novel solution approach combines stochastic aspects of the problem with a challenging discrete facility location problem in a three-phase algorithm. Computational results indicate a potential cost savings of hundreds of millions of dollars annually for long-distance companies.